SURVEI KONDISI FISIK WASIT BOLABASKET PENGCAB PERBASI KOTA SURABAYA (STUDI TERHADAP VOâ‚‚ MAKS WASIT BOLABASKET YANG MEMPUNYAI LISENSI C PENGCAB PERBASI KOTA SURABAYA TAHUN 2012) - Bachtiar, Amin; Wiriawan, Oce (Jurnal Prestasi Olahraga, 2013)
The purpose this research is to determine the capacity of VO ? max. With the approach of descriptive studies to illustrate specific phenomena. This study used samples of 15 refereed by calculating the average (mean), frequency and percentage.Based on the problems that have been formulated and in terms of research objectives, this research was a quantitative research. Surveying the physical condition of pengcab perbasi basketball referee (the study of VO ? max licence C basketball referee of pengcab PERBASI Surabaya), the research design used in the form of test measurements was the multistage run test (multistasge fitness test).The results showed that the average levels of VO ? max licence C basketball referee of Pengcab PERBASI Surabaya is 42.04 ml / kg / min. When assessed individually, the result were: 5 referees (33.3%) meet the standart, 10 referees (66.7%) did not meet the standart